Pendidikan Islam dan Insan Kamil; Anatomi Pemikiran Muhammad Iqbal - Rohmah, Naily (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
Islamic education seems to be experiencing a stagnant movement, running in place. Even though the current global era requires Islamic education to come to the fore, holding scientific supremacy, as happened in the past, this backward situation has made Iqbal criticize Muslims to immediately renew their attitude to become progressive. Based on this, the author offers Muhammad Iqbal's thoughts regarding his concept for education and human beings. The research method used is qualitative with a Library Research approach or library research, the data analysis used is historical analysis and descriptive analysis. The results of this research show that according to Iqbal, Islamic education is seen as a total cultural force that influences the lives of individuals and groups of society. Iqbal has an opinion about the meaning of Islam. Insan Kamil, according to Iqbal, must go through four stages. The first is Love, Courage, Tolerance, and Faqr. In the perspective of Islamic education, Insan Kamil is divided into two parts, first, regarding Individuality, containing the human journey through various life tests. Which will mature and put the level of the human person in its place. Second, Character Education, regarding the formation of the basis for correct human thinking as a shaper of character and personality.